Deubiquitination Step in the Endocytic Pathway of Yeast Plasma Membrane Proteins: Crucial Role of Doa4p Ubiquitin Isopeptidase - Dupré, S. (American Society for Microbiology, 2001)
The Fur4p uracil permease, like most yeast plasma membrane proteins, undergoes ubiquitin-dependent endocytosis and is then targeted to the vacuole (equivalent to the mammalian lysosome) for degradation. The cell surface ubiquitination of Fur4p is mediated by the essential Rsp5p ubiquitin ligase. Ubiquitination of Fur4p occurs on two target lysines, which receive two ubiquitin moieties linked through ubiquitin Lys63, a type of linkage (termed UbK63) different from that involved in proteasome recognition. We report that pep4 cells deficient for vacuolar protease activities accumulate vacuolar unubiquitinated Fur4p. In contrast, pep4 cells lacking the Doa4p ubiquitin isopeptidase accumulate ubiquitin-conjugated Fur4p. These data suggest that Fur4p undergoes Doa4p-dependent deubiquitination prior to vacuolar degradation. Compared to pep4 cells, pep4 doa4 cells have huge amounts of membrane-bound ubiquitin conjugates. This indicates that Doa4p plays a general role in the deubiquitination of membrane-bound proteins, as suggested by reports describing the suppression of some doa4 phenotypes in endocytosis and vacuolar protein sorting mutants. Some of the small ubiquitin-linked peptides that are a hallmark of Doa4 deficiency are not present in rsp5 mutant cells or after overproduction of a variant ubiquitin modified at Lys 63 (UbK63R). These data suggest that the corresponding peptides are degradation products of Rsp5p substrates and probably of ubiquitin conjugates carrying UbK63 linkages. Doa4p thus appears to be involved in the deubiquitination of endocytosed plasma membrane proteins, some of them carrying UbK63 linkages.